Marmosets: Welfare, Ethical Use, and IACUC/Regulatory Considerations. (23rd February 2021) - Colman, Ricki J; Capuano, Saverio; Bakker, Jaco; Keeley, Jo; Nakamura, Katsuki; Ross, Corinna
Abstract: Use of marmosets in biomedical research has increased dramatically in recent years due, in large part, to their suitability for transgenic applications and utility as models for neuroscience investigations. This increased use includes the establishment of new colonies and involvement of people new to marmoset research. To facilitate the use of the marmoset as a research model, we provide an overview of issues surrounding the ethics and regulations associated with captive marmoset research, including discussion of the history of marmosets in research, current uses of marmosets, ethical considerations related to marmoset use, issues related to importation of animals, and recommendations for regulatory oversight of gene-edited marmosets. To understand the main concerns that oversight bodies have regarding captive biomedical research with marmosets, we developed a brief, 15-question survey that was then sent electronically to academic and biomedical research institutions worldwide that were believed to house colonies of marmosets intended for biomedical research. The survey included general questions regarding the individual respondent's colony, status of research use of the colony and institutional oversight of both the colony itself and the research use of the colony. We received completed surveys from a total of 18 institutions from North America, Europe, and Asia. Overall, there appeared to be no clear difference in regulatory oversight body concerns between countries/regions. One difference that we were able to appreciate was that while biomedical research with marmosets was noted to be either stable or decreasing in Europe, use was clearly increasing elsewhere.